THERMODYNAMIC CONTROL ON HYDROGEN CONCENTRATIONS IN ANOXIC SEDIMENTS - Hoehler T.M.; Alperin M.J.; Albert D.B.; Martens C.S. (My University, 1998)
Molecular hydrogen plays a central role in bacterially mediated anoxic sediment chemistry, as both an important electron transfer agent and a key thermodynamic control. We studied the response of hydrogen concentrations to changes in temperature, specific electron acceptor, sulfate concentration, and pH in a series of laboratory experiments using sediments from Cape Lookout Bight, North Carolina. Hydrogen concentrations were found to depend significantly on each of these factors in a fashion that suggests thermodynamic control. In general, the change in hydrogen concentrations was apparently driven by a necessity to maintain a constant ΔG for the predominant terminal electron-accepting process. We hypothesize this situation derives from highly competetive conditions that force terminal metabolic bacteria to operate right at their thermodynamic limits. The response of hydrogen to individual controls in the laboratory experiments was reflected in relatively quantitiative fashion in down-core, seasonal, and inter-environmental variations observed in sediment cores from Cape Lookout Bight and the White Oak River, NC.